â€œApplication of environmental accounting reporting practices and problems regarding the presentation of it in Bangladeshâ€ (A case study on fossil-fuel sector) - Sultana, Reajmin (European Scientific Journal, ESJ, 2017)
Environmental accounting and reporting is an emerging concept in Bangladesh, although many countries in the world, either developed or developing, are already practicing environmental accounting and reporting in their fossil-fuel sector. Fossil energy resources in Bangladesh consist primarily of natural gas. This study deals with what types of data are required & how these will be presented in environmental accounting. It attempts to portray progress and drawbacks of Petrobangla Companies in respect of environmental accounting practices & tries to provide suggestions for better reporting practices. As there is a sustainability problem in energy sector, specially fossil-fuel sector of Bangladesh and the situation of pollution of Bangladesh is huge, environmental accounting practice is crying need to solve these types of problem in Bangladesh.